English literary studies: Islamic perspective and method - Hasan, Md. Mahmudul (2014)

(untitled)
There is a tendency to associate English studies with western value systems, secularism and anti-Islamic practices, and even with western Christendom. In response to this, scholars of postcolonial studies employ the twin strategy of ‘abrogation’ and ‘appropriation’ to dismantle the original intent of introducing English studies and, simultaneously, to create platforms of self-assertion and resistance. Islamization of English literary studies proponents propose a similar remedy to protect (Muslim) practitioners of English literature from untoward cultural influences as well as to present the Islamic worldviews in relation to the life-worlds the literary texts presumably promote. This is part of the wider concept of the Islamization of human knowledge that functions across a broad range of subject areas and generally refers to a method of looking at various academic disciplines from Islamic perspectives and informs the reader about relevant Islamic teachings. Two other important aspects of this intellectual undertaking are Ihya’ al-turath al-Islami (reviving of Islamic heritage) and Islamizing the self, that is, saturating the self and others with Islamic character and values (akhlaq). It requires a similar approach for Islamizing English literature. In this paper I will focus on three areas of Islamizing English literary studies: 1. Molding the self and others with Islamic values; 2. Islamizing literary texts, that is, identifying predominant ideas inherent in them and looking at those from Islamic perspectives; and 3. Reforming the curriculum.